2020
DOI: 10.17159/sajs.2020/8608
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and spread of the banana fungus Fusarium oxysporum f. sp. cubense TR4 in Mozambique

Abstract: Fusarium wilt, caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc), poses a major threat to banana production globally. A variant of Foc that originated in Southeast Asia, called tropical race 4 (TR4), was detected on a Cavendish banana export plantation (Metocheria) in northern Mozambique in 2013. Foc TR4 was rapidly disseminated on the farm, and affected approximately half a million plants within 3 years. The fungus was also detected on a second commercial property approximately 200 km aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…The Cavendish somaclone GCTCV-218 for commercial cultivation under the name of Formosona, generated in 2004 by the Taiwan Banana Research Institute, is known to be tolerant to FOC TR4 and two other somaclonal variants of Cavendish called GCTCV-53 and GCTCV-119 [ 152 ]. In a recent study, tests with these Cavendish banana somaclones in northern Mozambique revealed that GCTCV-119 was more resistant to FOC TR4, but GCTCV-218 produced better bunches [ 5 ]. Another recent study obtained, through different combinations of plant regulators in a culture medium, two somaclones of the cultivar Prata-Anã, namely T2-1 and T2-2, which presented resistance to FOC race 1 in a greenhouse, characterizing an important result for the banana cultivation in Brazil since the pathogen FOC R1is present in most banana plantations and this cultivar is preferred by Brazilian consumers [ 153 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cavendish somaclone GCTCV-218 for commercial cultivation under the name of Formosona, generated in 2004 by the Taiwan Banana Research Institute, is known to be tolerant to FOC TR4 and two other somaclonal variants of Cavendish called GCTCV-53 and GCTCV-119 [ 152 ]. In a recent study, tests with these Cavendish banana somaclones in northern Mozambique revealed that GCTCV-119 was more resistant to FOC TR4, but GCTCV-218 produced better bunches [ 5 ]. Another recent study obtained, through different combinations of plant regulators in a culture medium, two somaclones of the cultivar Prata-Anã, namely T2-1 and T2-2, which presented resistance to FOC race 1 in a greenhouse, characterizing an important result for the banana cultivation in Brazil since the pathogen FOC R1is present in most banana plantations and this cultivar is preferred by Brazilian consumers [ 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Cavendish banana, which accounts for about 47% of global production, is the most traded [ 2 ]. In African regions, plantains comprise a significant and essential component, contributing considerably to food security and income generation for more than 70 million Africans [ 3 , 4 , 5 ]. Similarly, in Latin America and the Caribbean, 62% of total banana and plantain production (20 million tons) is consumed locally, and approximately 6.8 million tons of plantains are produced, of which 72% are traded on international markets, indicating the enormous importance of these crops for local food and food security throughout the region [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of GCTCV 218 is consistent with previous field trials conducted in the NT, where high disease incidence due to Foc TR4 was observed [ 29 , 31 , 39 ]. GCTCV 218 has shown some resistance to Foc TR4 in naturally infested field conditions, with its deployment in the Philippines, Taiwan and Mozambique as a means to minimise losses due to the wilt disease while still producing good quality bunches [ 5 , 26 , 48 , 49 ]. The contrasting results of GCTCV 218 between the Australian trials to those in the Asia and Africa is likely due to the higher inoculum pressure and its uniform distribution with all plants inoculated at planting in the Australian trials, leading to increased mortality and disease severity as a result.…”
Section: Discussionmentioning
confidence: 99%
“…When contaminated water is used for irrigation or water flows from infested to Foc-free areas, the pathogen may contaminate banana production extensively [ 6 ]. For instance, Fusarium wilt was reported to rapidly increase after heavy rainfall in both the Philippines [ 7 ] and Mozambique [ 8 ]. The irrigation of banana plantings with contaminated water from the Pearl River in China [ 9 ] was also reported to have significantly contributed to the spread of Foc tropical race 4 (TR4) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%